Determination of body width in brown and white layer pullets by image analyses. Issue 3 (4th May 2017) - Giersberg, M. F.; Kemper, N.; Hartung, J.; Schrader, L.; Spindler, B.
ABSTRACT: 1. Specific legal requirements for keeping pullets are not available in the European Union. However, two of the most important rearing factors for pullets are sufficient perching and feeder space. Both factors represent horizontal space dimensions which derive from the body width of the birds. 2. The body width of two strains of layer pullets (brown (BL) and white (WL) layer pullets) based on the measurement of distances in digital images was conducted on front-view digital photographs of BL and WL pullets taken at 8, 12 and 19 weeks of life. 3. Depending on live weight, age and body position, BL pullets measured an average body width between 10.70 ± 1.10 and 13.96 ± 1.11 cm. The width of WL pullets ranged from 10.30 ± 0.86 to 13.00 ± 1.14 cm. 4. Compared with WL, BL pullets occupied more horizontal space during rearing. Age influenced the body width of BL and WL pullets at the end of rearing. The tested body positions of the pullets did not affect the measured body width. 5. The biometric data obtained in this study are a useful basis for developing legal requirements for pullets, especially for defining minimum perch width and feeder space allowances.